Bidirectional and Dynamic Relationships Between Social Isolation and Physical Functioning Among Older Adults: A Cross-Lagged Panel Model of US National Survey Data. (11th April 2021) - del Pozo Cruz, Borja; Perales, Francisco; Alfonso-Rosa, Rosa M; del Pozo-Cruz, Jesus
Abstract: Background: Previous studies examining unidirectional relationships between social isolation and physical functioning among older adults may be biased due to reverse causality. This study leveraged data from a US national sample of older adults and a novel estimation method to identify bidirectional associations between these 2 phenomena and their associated temporal dynamics. Methods: The analyses were based on 9 waves of panel data from a sample of adults aged 65 and older from the US National Health and Aging Trends Study ( n = 12 427 individuals) and a cross-lagged panel model. Social isolation was measured using the Social Isolation Index (SII) and physical functioning through the Short Physical Performance Battery (SPPB). Results: One SD increase in the SPPB was associated with a −0.013 SD decrease (95% confidence interval [CI]: −0.023 to −0.004) in the SII a year later, whereas 1 SD increase in the SII was associated with a larger −0.058 SD decrease (95% CI: −0.069 to −0.046) in the SPPB a year later. The SII→SPPB effect lasted for approximately 5 years, whereas the SPPB→SII lasted for approximately 3 years. Conclusions: This study confirmed the existence of statistically significant bidirectional associations between social isolation and physical functioning among older adults in the United States, net of reverse causation. Because the effect of social isolation dominates, the findings indicate that public health strategies to promote successful aging should prioritize interventions that enrich older adults' social networks. Furthermore, the effect time horizons yielded by the model point to the optimal timing for the re-delivery of interventions.